‘Best Known Example of Relativity in Literature’: Personal Supertext of L.N. Tolstoy in V.V. Nabokov’s Novel “Pnin” - A. O. Drozdova (Научный диалог, 2024)
This article addresses the issue of interpreting the work and biographical myth of L.N. Tolstoy in V.V. Nabokov’s novel “Pnin.” The aim of the study is to examine how through the reconstruction of Tolstoy’s personal supertext, Nabokov conveys his philosophy of time. This question is relevant in the context of studying Nabokov’s historiosophy and the writer’s reflection on his own literary genealogy. The analysis reveals that in Nabokov’s reception, Tolstoy is a national genius who was able to recreate the effect of natural time flow. Explicit references to Tolstoy and his biography allow for correlating the characters’ reading experience and their perception of time: from frozen time during reading-performance to the reverse flow of time during co-creative reading. The motifs of Tolstoy’s works actualize the key problem of the relativity of time for Nabokov. Although the unreliable narrator emphasizes the power of time and fate over the lonely hero, in reality, Pnin has access to multiple temporal dimensions. Just like in “Anna Karenina,” the technique of temporal synchronization highlights the interconnectedness of characters’ fates. Tolstoy’s personal supertext enables Nabokov to understand the theme of family as a timeless connection between people that defines the characters’ place in the world.